Decision-making in the management of an incomplete urethral duplication in a young male - Treviño Rangel, Rogelio de Jesús; Bodden Mendoza, Byron Anthony; Cantú Salinas, N.; García Rodríguez, María de los Ángeles (UANL. Facultad de Medicina, 2015)
This is a case report of a 27-year-old Mexican man complaining of a double urethral meatus located at the tip of the glans. Material and methods: An exhaustive physical examination was performed together with an intravenous excretory urography and retrograde urethrogram in order to evaluate the case properly. Results: The patient presented an incomplete urethral duplication type 1B according to Effmann’s classification. Conclusion: The lack of symptoms as well as the absence of significant clinical or functional repercussion in the patient led us to recommend therapeutic abstention for the time being.